Analisis Pengembangan Desa Wisata Tondok Bakaru Kabupaten Mamasa - Medyawati, Citra; Salim, Agus; Ruslan, Rusneni (Fakultas Teknik Universitas Bosowa, 2023)
This study aims to find out what are the factors that cause the development of the Tondok Bakaru Tourism Village in Mamasa Regency and what are the strategies for developing the Tondok Bakaru Tourism Village in the Regency. Mamasa was then analyzed using multiple linear regression tests and SWOT analysis. From the results of multiple regression analysis, the factors that cause the undeveloped Tondok Bakaru Tourism Village are accessibility, and human resources (HR), and the development strategy for the Tondok Bakaru Tourism Village, mamasa district with the SWOT analysis approach, namely strategies for increasing and developing tourist attractions, empowerment strategies human resources (HR), Strategy for making tour packages (nature, culture, education), Strategy for improving and monitoring facilities and infrastructure, Strategy for increasing and improving accessibility.